The Effect of Motivational Interviewing Approach on Motivation and Autonomy of Tb Patient in Lung Tb Treatment - Pembronia Nona Fembi (Universitas Airlangga, 2013)
Introduction: Attitude, knowledge, social support, motivation, and autonomy of client with lung TB are important elements for the successfulness of lung TB treatment. Client with lung TB have disadvantage not only from health aspect, but also from social and economy aspects. This research aimed to analyze the effect of giving motivational interviewing on attitude, knowledge, social support, motivation, and autonomy in lung TB treatment.Method: Research design was quasy experiment with pre-post test control group design. Population was TB patients who visited Puskesmas Kopeta and Puskesmas Wolomarang, Sikka, NTT. Sample were taken by using purposive sampling, 30 responden were included, devided into treatment group (15 persons) and control group (15 persons). Independent variable was motivational interviewing approach, while the dependent variables were motivation, autonomy, knowledge, attitude, and social support according to patient perception. Data were collected using questionnaire. Data were analyzed using MANOVA with signi fi cance level ≤ 0.05. Result: Research result showed that motivational interviewing had significant effect to client’s knowledge (p = 0.000), social support (p = 0,003), motivation (p = 0.000), and autonomy (p = 0.000). But, motivational interviewing had no significant effect to attitude (p = 0.811).Discussion: Giving motivational interviewing can improve motivation and autonomy of lung TB patient in treatment. Further researchers can perform similar research with pure experiment research by modifying other variable and the respondents involving family and with greater sample size.